1998
DOI: 10.1111/j.1749-6632.1998.tb09691.x
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Ganglioside for Acute Ischemic Stroke: Trial Design Issues

Abstract: GM1 ganglioside decreases the severity of ischemic brain lesions in experimental models, although the mechanism is uncertain. In clinical trials involving patients with stroke, efficacy has been reported in some but not in others. However, some of the latter also showed efficacy after analyses not planned before the trial began. Analyses of the trials done to date revealed design differences sufficiently large so as to preclude meta-analysis of the results. Moreover, flaws in these studies may account for some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In this regard, previous clinical trials in which the ganglioside was used for the treatment of other conditions (35,(53)(54)(55) demonstrated that GM1 is safe to use in patients, even when administered by intraventricular infusion (56), and potential adverse effects are rare (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, previous clinical trials in which the ganglioside was used for the treatment of other conditions (35,(53)(54)(55) demonstrated that GM1 is safe to use in patients, even when administered by intraventricular infusion (56), and potential adverse effects are rare (35).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the pivotal role of gangliosides in the nervous system and in cell signaling, defects in their biosynthetic pathway lead to a severe infantile neurodegenerative disorder characterized by progressive brain atrophy, chorea, and epilepsy (35), symptoms that are also common to the juvenile form of HD (36).…”
mentioning
confidence: 94%
“…In HD, where endogenous levels of the ganglioside are reduced, GM1 is likely to have multiple beneficial effects, by restoring normal ganglioside content and by targeting multiple aspects of the HD pathology: from cell signaling and AKT activation to mHtt phosphorylation, susceptibility to apoptosis, and potentially also axonal transport and neurotrophin release and excitotoxicity. Importantly, previous clinical trials that have tested the effects of GM1 in patients with stroke (Alter, 1998), Parkinson's disease (Schneider, 1998), and spinal cord injury (Chinnock and Roberts, 2005) have shown that the compound is relatively safe to use. Possible potential adverse effects, such as the development of a peripheral neuropathy known as Guillain-Barré…”
Section: Discussionmentioning
confidence: 99%
“…Mocchetti Neurotrophic function of exogenous gangliosides extracellular events involved in apoptosis, which will be presented later. The use of gangliosides in humans is still limited despite the positive outcome of clinical trials showing that GM1 and other gangliosides, either alone or in combination with other neuroprotective agents, reduce neuronal damage after stroke [59] and spinal cord trauma [60]. Major setbacks preventing a wide use of gangliosides in human neurodegenerative disorders are concerns about side effects, such as the potential of GM1 to cause allergic reactions [61] or an acute Guillain-Barré syndrome [62,63].…”
Section: Apoptosis Ischemic Stroke and Spinal Cord Injurymentioning
confidence: 99%